Soluble B and T Lymphocyte Attenuator Correlates to Disease Severity in Sepsis and High Levels Are Associated with an Increased Risk of Mortality. - Anna Lange; Jonas Sundén-Cullberg; Anders Magnuson; Olof Hultgren (PLoS ONE, 2017)
B- and T-lymphocyte Attenuator (BTLA), Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and Programmed Death 1 (PD-1) are co-inhibitory receptors that regulate T cell activation. In the present study of ICU-treated patients we measured plasma concentrations of their soluble isoforms, with the aim to evaluate their potential as sepsis biomarkers and utility as prognostic indicators.101 patients with sepsis, 28 patients with non-infectious critical illness (ICU controls) and 31 blood donors (healthy controls, HC) were included in the study. Plasma concentrations of soluble BTLA (sBTLA), CTLA-4 (sCTLA-4) and PD-1 (sPD-1) were measured with ELISA in serial blood samples. Comparisons were made with Mann-Whitney U test and correlations were assessed with Spearman's Rank correlation test. Cox proportional hazard models, with sBTLA and sPD-1 as fixed and sBTLA as time-varying covariates, were used to determine association with 28-day mortality.sBTLA levels were significantly higher in the sepsis cohort (median 14 ng/mL, IQR 8-29) compared to ICU controls (9 ng/mL, IQR 5-26, p = 0.048) and HC (2.9 ng/mL, IQR 0.9-9.1, p<0.01), and correlated to SOFA score. sBTLA levels were higher in 28 day sepsis non-survivors than in survivors (baseline median 28 ng/mL, IQR 13-41 vs 13 ng/mL, IQR 8-23, p = 0.04). After adjustment for age and comorbidities, the relative risk of 28 day mortality was nearly 5-fold higher in sepsis patients with a baseline sBTLA > 21 ng/mL, compared to those with a level below this threshold. sBTLA was even more associated with mortality in the time-varying analysis. sPD-1 levels were lower in the sepsis cohort compared to HC but not compared to ICU controls and were not associated with mortality. sCTLA-4 was detectable in only one subject.Plasma concentrations of soluble BTLA were increased early in sepsis/septic shock and correlated to severity of disease. A baseline concentration >21ng/mL was associated with a poor prognosis.